Neointimal hyperplasia after endoluminal injury in mice is dependent on tissue factor- and angiopoietin-2 dependent interferon gamma production by fibrocytes and macrophages - Chen, Daxin; Li, Ke; Wei, Lin-Lin; Ma, Ning; McVey, John H.; Dorling, Anthony (Frontiers in Immunology, 2024)
Background: The intimal hyperplasia (IH) and vascular remodeling that follows endovascular injury, for instance after post-angioplasty re-stenosis, results in downstream ischaemia and progressive end organ damage. Interferon gamma (IFNg) is known to play a critical role in this process. In mouse models we have previously shown that fibrocytes expressing tissue factor (TF) are recruited early to the site of injury. Through thrombin generation and protease activated receptor-1 (PAR-1) activation, fibrocytes secrete angiopoietin-2, stimulate neointimal cell proliferation, inhibit apoptosis and induce CXCL-12 production, all of which contribute to the progressive IH that then develops. In this study we investigated the relationship between TF, angiopoietin-2 and IFNg. Methods and Results; IH developing in carotid arteries of wild-type mice 4 weeks after endoluminal injury contained a significant proportion of IFNg+ fibrocytes and macrophages, which we show, using a previously defined adoptive transfer model, were derived from circulating CD34+ cells. IH did not develop after injury in IFNgdeficient mice, except after transplantation of WT bone marrow or adoptive transfer of WT CD34+ cells. In vitro, CD34+ cells isolated from post-injury mice did not express IFNg, but this was induced when provided with FVIIa and FX, and enhanced when prothrombin was also provided: In both cases IFNg secretion was TF-dependent and mediated mainly through protease activated PAR-1. IFNg was predominantly expressed by fibrocytes. In vivo, all IFNg+ neointimal cells in WT mice co-expressed angiopoietin-2, as did the small numbers of neointimal cells recruited in IFNg-/-mice.Adoptively transferred WT CD34+ cells treated with either an anti-TIE-2 antibody, or with siRNA against angiopoetin-2 inhibited the expression of IFNg and the development of IH.Conclusions: TF-dependent angiopoietin-2 production by newly recruited fibrocytes, and to a lesser extent macrophages, switches on IFNg expression, and this is necessary for the IH to develop. These novel findings enhance our understanding of the pathophysiology of IH and expose potential targets for therapeutic intervention.